The FRUIT : food, fertility, fascination - Jutta, Mariam (Universiti Putra Malaysia, 2012)
Sensulato, and botanically speaking, fruit is an assemblage of standard components intended for the reproduction of a plant organism. A fruit holds the seed(s) destined to produce a new generation, irrespective of its edible qualities (Bell,1998). Fruit, in the widest and yet most basic context, is nothing but a ripened ovary with seed structures attached to it (Harris & Harris, 2001), and by this virtue both conception and cradle of new life.